Effect of percutaneous radiofrequency ablation after thoracoscopic pleurodesis for treating non‐small cell lung cancer patients with malignant pleural effusion and/or pleural dissemination. Issue 5 (7th June 2016) - Liu, Baodong; Liu, Lei; Hu, Mu; Qian, Kun; Li, Yuanbo
Abstract : Background: The purpose of this study was to retrospectively evaluate percutaneous radiofrequency ablation (RFA) combined with palliative thoracoscopic pleurodesis (TP) for malignant pleural effusion and/or pleural disseminated non‐small cell lung cancer (NSCLC), diagnosed by thoracoscopy. Methods: The study was composed of 40 patients with primary NSCLC with malignant pleural effusion and/or pleural dissemination recognized for the first time during thoracoscopic exploration. Twenty patients received TPR (TP plus RFA group), while the remaining 20 patients who underwent TP (TP group) represented the control. We evaluated technical success, safety, initial response rate, progression‐free survival (PFS), and overall survival (OS). Results: No procedure‐related deaths or major complications occurred in any of the 22 ablation procedures. Complete response was observed in 15% of patients, partial response in 50%, stable disease in 25%, and progressive disease in 15% of patients. The mean follow‐up was 15.5 months. The PFS at years one, two, and three were 77.5%, 38.8%, and 25.8%, respectively. The OS at years one, two, and three were 77.5%, 41.4%, and 27.6%, respectively. The PFS and OS were longer in the TP‐R group, indicating a better prognosis than that of the patients who underwent TP only (OS 24 vs. 18 months, P = 0.030; PFS 22 vs. 15 months, P = 0.036). Conclusions: Palliative TP combined with percutaneous RFA is a safe, feasible, and effective procedure in patients with malignant pleural effusion and/or pleural disseminated NSCLC.